Direct comparison of gamma, electron beam and X-ray irradiation effects on single-use blood collection devices with plastic components. (March 2021) - Fifield, Leonard S.; Pharr, Matt; Staack, David; Pillai, Suresh D.; Nichols, Larry; McCoy, James; Faucette, Tony; Bisel, Tucker T.; Huang, Min; Hasan, Md Kamrul; Perkins, Lucas; Cooley, Scott K.; et al.
Abstract: Effective sterilization methods for single-use devices are a growing need for the medical industry. Concerns with safety, throughput and source availability, however, prompt prudent contingency planning for gamma irradiation of devices suited for radiation sterilization. Electron beam (e-beam) and X-ray represent two alternatives to gamma radiation if they can be confirmed to be compatible with sterilization of the devices. To address this question, the effects of sterilization-relevant doses of e-beam and X-ray radiation are directly compared to the effects of gamma radiation using two prototypical commercial devices currently sterilized using cobalt-60 gamma radiation. These devices include components that comprise six distinct polymer materials commonly used in the medical device industry. The devices investigated are the Becton, Dickinson and Company (BD) Vacutainer TM Plus tube, comprised of low-density polyethylene, chlorobutyl rubber, and polyethylene terephthalate components; and the BD Vacutainer TM Push Button Blood Collection Set, containing polypropylene, polyolefin elastomer, and polyvinyl chloride components. Changes in functionality, discoloration and select mechanical properties of components of each device were measured following exposure to targeted doses of 15, 35, 50 and 80 kGy. A statistical analysis was performed to determine if the effects of e-beam or X-ray radiation differ from the effects of gamma radiation for the properties considered. No devices were found to fail the functional performance tests at any of the doses considered. Small, but statistically significant differences were observed in device discoloration from e-beam, X-ray and gamma radiation following processing for certain materials at certain dose levels. Both e-beam and X-ray irradiation appear as viable alternatives to gamma irradiation for sterilization of the medical devices and materials considered. Highlights: Electron beam and X-rays are alternatives to gamma for radiation sterilization. E-beam, X-ray and gamma radiation effects on medical devices were compared. Blood collection tubes and sets were exposed to 15, 35, 50 and 80 kGy doses. Function, color, and mechanical properties were measured versus irradiation. Results support both e-beam and X-ray as viable irradiation sterilization options.